Ketahanan Likuiditas dan Solvabilitas di Tengah Tekanan Profitabilitas: Analisis Rasio Keuangan PT Hanjaya Mandala Sampoerna Tbk Tahun 2024–2025 - Yudhi Kusumo Wibowo; Chersilou Chersilou; Yanaria Amnunuh; Sri Hermuningsih (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the financial performance of PT Hanjaya Mandala Sampoerna Tbk for the 2024–2025 period using a financial ratio analysis approach, which includes liquidity, activity, solvency, and profitability ratios. The research method employed is descriptive quantitative, utilizing secondary data in the form of the company's audited financial statements for the years 2024 and 2025. The results indicate that the liquidity ratio experienced an increase, as shown by the current ratio rising from 1.63 to 1.76 and the quick ratio from 0.68 to 0.77, although the quick ratio remains below the ideal standard. The activity ratio showed a decrease in inventory turnover from 4.56x to 4.29x, but the total asset turnover increased from 1.23x to 1.27x. The solvency ratio improved, with the debt-to-asset ratio decreasing from 45.01% to 44.95% and the debt-to-equity ratio from 81.87% to 81.67%, indicating a reduced dependence on debt.Meanwhile, the profitability ratio revealed a contradictory phenomenon: gross profit increased by 11.24% to Rp20.62 trillion, but net profit fell by 0.55% to Rp6.61 trillion due to a 14.44% increase in general and administrative expenses, a 51.90% decline in finance income, a 301% spike in other expenses, and a 38.08% increase in tax expenses. The profit margin was recorded to increase from 5.64% to 5.89%, while ROA and ROE experienced slight decreases from 12.89% to 12.82% and from 23.44% to 23.29%, respectively. Overall, PT Hanjaya Mandala Sampoerna Tbk maintains a sound and stable financial condition, but needs to control its operating expenses to improve net profit in the future.